Oma, K.A. (2018). The sheep people. The ontology of making lives, building homes and forging herds in early Bronze Age Norway. Equinox Publishing Ltd, Sheffield, UK; Bristol, CT. - David G. Anderson (Primitive Tider, 2019)
Bokanmeldelse